2018
DOI: 10.21608/ejhc.2018.151633
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum: post-operative effect on women's recovery and bowel motility following gynecologicabdominal surgery

Abstract: Background: Ileus commonly happens post abdominal surgery and is associated with complication and may delay recovery. The study is hypothesized that chewing gum decreases postoperative ileus by improving early recovery of gastrointestinal function. Aim: The study aims to investigate the effect of chewing gum on the postoperative recovery of gastrointestinal function after gynecological and abdominal surgery. Methods; Design: A quasi-experimental research design. Setting: the study was conducted at the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Huang et al, also concluded that the use of intravenous Dexmedetomidine accelerates the return of bowel motility after laparoscopic nephrectomy surgery [ 9 ]. Various studies have also confirmed the effect of chewing gum in improving the return of bowel motility [ 1 , 4 , 10 13 ]. However, in textbooks, there is no standard treatment for postoperative ileus, and currently, surgeons do not know any other standard method to suggest to patients other than reassurance about the return of bowel motility [ 3 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Huang et al, also concluded that the use of intravenous Dexmedetomidine accelerates the return of bowel motility after laparoscopic nephrectomy surgery [ 9 ]. Various studies have also confirmed the effect of chewing gum in improving the return of bowel motility [ 1 , 4 , 10 13 ]. However, in textbooks, there is no standard treatment for postoperative ileus, and currently, surgeons do not know any other standard method to suggest to patients other than reassurance about the return of bowel motility [ 3 ].…”
Section: Introductionmentioning
confidence: 98%
“…Bowel motility disorder after abdominal surgeries is the most common cause of delayed discharge of patients from the hospital [ 4 ]. The delay in the return of bowel motility, which is seen in almost half of the patients after surgery, is a nervous, hormonal, or medicinal process, and has various consequences such as abdominal distention, decreased bowel sounds, delayed gas passing and defecation, increased pain after surgery, delay in wound healing, nausea and vomiting, loss of appetite, and delay in starting oral feeding [ 4 , 5 ]. In addition to affecting the patient after surgery, this disorder also significantly increases the cost of healthcare systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%